The Ummi Method As an Effort to Improve the Ability of Students to Read Al Qur’an at Pesantren Madinah Al-Hijrah - Hidayatullah, Agus; Rosita, Desyi; Jubaedah, Siti (Bulletin of Science Education, 2023)
The Ummi method is an innovative approach developed as an effort to improve students' ability to read the Koran. This method is designed to take into account children's learning characteristics and utilizes the principles of Islamic education. This research aims to evaluate the effectiveness of the Ummi Method in improving students' ability to read the Al-Qur'an. This research uses a qualitative and quantitative approach involving a number of students at an Islamic boarding school. Data was collected through observation, interviews, and Al-Qur'an reading ability tests before and after implementing the Ummi Method. The results of the research show that the Ummi Method has a significant positive impact on increasing the ability to read the Al-Qur'an in students. Ummi's method combines interactive, creative learning and is based on Islamic values. In its application, this method uses various learning media, including Islamic story books, learning songs, and educational games. In addition, the personalization approach in the Ummi Method allows for adjustments to learning according to the individual needs of students. In this context, the Ummi Method does not only focus on the technical aspects of reading, but also pays attention to understanding the contents of the Koran and the application of moral values ??in everyday life. Overall, the Ummi Method can be considered an effective and holistic effort to improve students' ability to read the Qur'an, with the potential to become a model for a sustainable learning approach in the Islamic education environment. Keywords: Ummi Method, Improving Reading Al Qur’an, Ummi Method Learning